تحديات التجارة الإلكترونية للنظم الضريبية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر ثورة المعلومات الأساس في ظهور ونمو العولمة القائمة على تحرير تجارة السلع والخدمات، وإزالة القيود الجمركية والحدود الاقتصادية للدولة. وتحويل الأسواق المحلية إلى سوق عالمية مفتوحة، مما يسهم في الاعتماد على شبكة الاتصالات في دعم ومساندة التجارة العالمية، مقابل ذلك نلاحظ أن ظهور التجارة الإلكترونية قد خلق تحديات اقتصادية بما فيها التحديات الضريبية للنظم الضريبية في مختلف الدول المتقدمة منها والنامية. لقد أوجز هذا البحث تلك التحديات بنوعيها وسلط الضوء على عدم قدرة نظام ضريبة الدخل أو الضرائب غير المباشرة الأخرى على مجاراة التطور الحاصل في ميدان التجارة الإلكترونية سواء في الدول المتقدمة أو النامية، كما حدد الملامح الأساسية لآلية المعالجة الضريبية المستقبلية والأسس الواجب أخذها بعين الاعتبار لتحقيق التوازن بين تطور التجارة الإلكترونية والتغير المطلوب في النظم الضريبية. The information revolution is considered the basis for the appearance and the development of globalization which depends on the decontrol of trade commodities and services, leading to the elimination of the restrictions of customs and the international economic boundaries. This led to changing the national markets into international open market. Dependence on the internet helps to support international trade. We also notice that the appearance of electronic commerce has created economic challenges including the taxation systems in all developed and developing countries. This research summarizes these challenges and focuses on the inability of the income taxation system, or the indirect taxes to follow the development in the electronic commerce in all the countries. It also identifies the main features for future taxation manipulation, and the measures that should be taken to achieve balance between the development of the electronic commerce and the necessary change in the taxation systems.